Scientific instruments between East and West
1 online resource.
Keywords: Scientific Instruments between East and West is a collection of essays on aspects of the transmission of knowledge about scientific instruments and the trade in such instruments between the Eastern and Western worlds, particularly from Europe to the Ottoman Empire. The contributors, from a variety of countries, draw on original Arabic and Ottoman Turkish manuscripts and other archival sources and publications dating from the fifteenth to the twentieth centuries not previously studied for their relevance to the history of scientific instruments. This little-studied topic in the history of science was the subject of the 35th Scientific Instrument Symposium held in Istanbul in September 2016, where the original versions of these essays were delivered. Contributors are Mahdi Abdeljaouad, Pierre Ageron, Hamid Bohloul, Patrice Bret, Gaye Danışan, Feza Günergun, Meltem Kocaman, Richard L. Kremer, Janet Laidla, Panagiotis Lazos, David Pantalony, Atilla Polat, Bernd Scholze, Konstantinos Skordoulis, Seyyed Hadi Tabatabaei, Anthony Turner, Hasan Umut, and George Vlahakis.